Importance of Financial Econometric Models in Analyzing the Performance of Equity Investments in the Capital Market : A Study - Aileni, Vidyadhar Reddy; Mastipuram, Ramesh; Kanumuri, Rama Raju (Indian Journal of Research in Capital Markets, 2024)
The study underlined the various financial econometric techniques to evaluate the performance of financial investments made in capital markets. The present research work studied the market trends in capital markets and analyzed the factors influencing the market movements. The study also evaluated the risk characteristics of investors and the investments made in the capital market. The study aimed to estimate the returns of investments based on the risk characteristics by use of financial econometrics after evaluating the risk characteristics. The study project also looked at investment volatility and identified the elements that affected it, as well as the influence of volatility on investments and the projected effect of volatility on capital market investments. The current research work performed financial modeling using the different applications and techniques of financial econometrics, studied the volatility and risk characteristics of investments, and developed solutions for minimizing the risk of investors. The study assessed the performance of stocks depending on the company and industry and examined the performance of several chosen firm stocks. It recommended that investors use financial econometric modeling to optimize their investment returns.